Dificuldades de aprendizagem em estequiometria: uma proposta de ensino apoiada na modelagem - Santos, Livia Cristina dos (2013)
In order to learn/teach chemistry some themes are relevant, like the stoichiometry, which consists in the study of the weight ratios in the combination of elements and compounds between themselves. This is an underlying subject in the understanding/representation/forethought of chemical reactions. Considering these aspects, our study presents a modeling-based proposal to develop the content of stoichiometry with prospective chemistry teachers. With this aim, we have made a review of literature, which we considered when tried to identify the learning difficulties using both quizzes and pedagogical tests, and then, from those difficulties we could propose a teaching unit for this concept and, consequently the evaluation of our proposal. The participants were chemistry undergraduates at the Universidade Federal do Rio Grande do Norte (UFRN) from assorted levels. As a methodological framework, we rely on the discursive textual analysis to characterize the speech of participants. As main results we observed ideas of appearance or disappearance of matter during chemical transformations, disregard of stoichiometric proportions when using drawings to represent the microscopic level of a reaction and confusion between the magnitude amount of matter and other magnitudes such as mass and volume. The final product is a sequence of instruction, based on the modeling previous research literature , with the goal of improving students ability to articulate the macroscopic and submicroscopic levels of representation of the matter